2010
DOI: 10.1159/000314927
|View full text |Cite
|
Sign up to set email alerts
|

Parry-Romberg Syndrome Associated with Localized Scleroderma

Abstract: Parry-Romberg syndrome is a rare neurocutaneous disorder of unknown origin. It is characterized by progressive facial hemiatrophy and frequently overlaps with a condition known as linear scleroderma ‘en coup de sabre’. Neurological involvement is frequently described in these patients, including migraine, facial pain and epilepsy, which represent the commonest neurological conditions, sometimes associated with brain abnormalities ipsilaterally to the skin lesions. We present a case of Parry-Romberg syndrome wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
(37 reference statements)
0
22
0
2
Order By: Relevance
“…8,24,29,30 Degenerative alterations of vascular endothelia have been identified on electron microscopy. 24 PRS has been associated with bandlike alopecia, 31 homolateral segmental vitiligo, 32 hyperpigmentation, 20,33 port-wine stain, 14 Klippel-Tr enaunay syndrome, 14 lupus profundus, 34 morphea, [35][36][37] and linear scleroderma en coup de sabre (LSCS) (Fig 3) 14,16,28,[38][39][40][41][42][43][44] (Table I).…”
Section: Cutaneous Manifestations Pathology and Dermatologic Associmentioning
confidence: 99%
See 1 more Smart Citation
“…8,24,29,30 Degenerative alterations of vascular endothelia have been identified on electron microscopy. 24 PRS has been associated with bandlike alopecia, 31 homolateral segmental vitiligo, 32 hyperpigmentation, 20,33 port-wine stain, 14 Klippel-Tr enaunay syndrome, 14 lupus profundus, 34 morphea, [35][36][37] and linear scleroderma en coup de sabre (LSCS) (Fig 3) 14,16,28,[38][39][40][41][42][43][44] (Table I).…”
Section: Cutaneous Manifestations Pathology and Dermatologic Associmentioning
confidence: 99%
“…147 Moreover, both disorders have comparable neurologic and ophthalmologic findings, 147 and both may respond to immunosuppressive treatment. 76,112,151,152 Furthermore, both conditions may show overlap or transition 14,17,28,43,44,58 ; although LSCS and PRS were found to coexist in many patients, [153][154][155][156] some have described patients with LSCS converting with time to PHA (Fig 4). 155,157 The prevalence of LSCS in conjunction with PRS is uncertain, but has been reported to range from 36.6% to 53.6%.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…142,143,162,163 There have also been reports indicating that anticonvulsants and antidepressants effectively mitigated symptoms. 144,164,165 One case report indicated that corticosteroids and azathioprine were ineffective for treating optic papillitis. 145 One case of cerebral vasculitis, which improved with mycophenolate, has been reported.…”
mentioning
confidence: 99%
“…Antinuclear antibodies (ANA) are detected in 50% of patients. Neurological disorders including migraine, trigeminal nerve palsy and epilepsy occur in 20%, and ophthalmological complications in 15% of patients [25]. Sometimes the disease is associated with hair loss and premature greying [24].…”
Section: Twardzina Linijnamentioning
confidence: 99%
“…U 50% pacjentów obecne są przeciwciała przeciwjądrowe ANA. Zaburzenia neurologiczne w postaci migreny, porażenia nerwu trójdzielnego i padaczki występują u 20% chorych, z kolei powikłania okulistyczne u 15% [25]. Niekiedy dochodzi …”
Section: Twardzina Linijnaunclassified